Job stress as a predictor of employee health - Ismail, Azman; Abu Hasan, Norhafizah; Chin, Yu-Fei (Melissa); Ismail, Yusof; Abu Samah, Ainon Jauhariah (Faculty of Economic Sciences Lucian Blaga University of Sibiu, 2013)
This study was conducted to measure the relationship between job stress and employee health. A survey method was employed to collect self-administered questionnaires from employees in established universities in Sarawak, Malaysia. The outcomes of SmartPLS path model revealed three important findings: first, role ambiguity was positively and significantly related to employee health. Second, role conflict was positively and significantly related to employee health. Third, role overload was positively and significantly related to employee health. Statistically, the result demonstrates that the level of job stress has been an important predictor of employee health in the studied organizations. The paper includes discussions, implications and conclusion